Biosecurity Level of Poultry Production Cluster (PPC) in West Java, Indonesia - Martindah , Eny; Ilham, Nyak; Basuno, Edi (International Journal of Poultry Science, 2014)
A biosecurity assessment was conducted on poultry farms in Subang and Ciamis districts in West Java Province, Indonesia. The objective of the study was to assess biosecurity practices and the level of biosecurity across clustered and non-clustered poultry farms. A biosecurity scoring test which was developed in previous studies on avian influenza control practices, was used in this study. One out of every five farms was randomly chosen in poultry farms in Subang and Ciamis. The results of the study showed that individual farmers in both clustered and in non-clustered poultry farms did not apply biosecurity standard operational procedures (SOP) in optimal ways. In Subang, clustered poultry farms has an average score of 19 points, while non-clustered farms had an average score of 16.70. Two clustered poultry farms in Ciamis that are PPC I Ciamis and PPC II Ciamis had an average score of 7.40 and 9.97, respectively, from total score of 42 points. Therefore, all farmers in the study sites scored less than 50% in practicing biosecurity measures. Farmer did not properly apply biosecurity SOP partly because the company was already responsible for all disease preventions measures through vaccination program and provides all input for poultry production. It is recommended to reconsider of the involvement of farm workers in PPC and non-PPC as well as related stakeholders to follow some basic principles of biosecurity: (i) keep poultry in good condition, (ii) keep poultry in a protected environment and (iii) control the entries of outsiders to the farm.